Physical Inactivity from the Viewpoint of Evolutionary Medicine - Sylvia Kirchengast (MDPI AG, 2014)
Activity patterns of recent Homo sapiens are characterized by a sedentary life style and consequently by exercise deficiency. This lack of physical activity increases the risk of various chronic non-communicable diseases and reduces health related quality of life. From the perspective of evolutionary medicine, the high rates of non-communicable disease among contemporary industrialized populations may be interpreted as the result of a mismatch between high rates of physical activity in the adaptively relevant (ARE) and sedentary recent life circumstances. Public transport, cars, elevators, supermarkets and internet shopping diminished daily physical activities dramatically, therefore recent Homo sapiens suffer from the consequences of a convenient life style, which is completely new in our evolution and history. The only possibility to increase physical activity and enhance health and well-being is through sporting activities during leisure time.